Current advances of photobiomodulation therapy in treating knee osteoarthritis - Zhang, Yanlei; Ji, Quanbo (Frontiers in Cell and Developmental Biology, 2023)
Knee osteoarthritis (KOA) is manifested by low-grade joint inflammation, irreversible cartilage degeneration, subchondral bone remodeling and osteophyte formation. It is one of the most prevalent degenerative diseases in the elderly. KOA usually results in chronic joint pain, physical impairment even disability bringing a huge socioeconomic burden. Unfortunately, there is so far no effective interventions to delay the progression and development of KOA. There is a pressing need for explorations and developments of new effective interventions. Photobiomodulation therapy (PBMT), also known as low-level light therapy (LLLT), has attracted widespread attention in treating KOA because it is drug-free, non-invasive, safe and useful with rarely reported side effects. It provides the biological stimulatory effects primarily by enhancing the activity of mitochondrial cytochrome c oxidase. This stimulation, in turn, fosters cell proliferation and tissue regeneration. In addition to this, the paper provides a concise overview of the light parameters and the effectiveness of PBMT when applied in the treatment of KOA patients in clinical settings. It also delves into the experimental evidence supporting the modulatory effects of PBMT and its potential underlying mechanisms in addressing synovitis, cartilage degeneration, and pain resolution.